Optimalisasi Desa Wisata Melalui Festival Wisata Kuliner Di Desa Kedungpari Jombang - Shahna Naila Safira; Sumainah Fauziah (NEAR: Jurnal Pengabdian kepada Masyarakat, 2023)
The community service activities carried out in Kedungpari Village are aimed at optimizing the potential of village tourism. This study discusses optimization of tourist villages through culinary tourism festival activities, focusing on Kedungpari village. The main purpose of this study is to increase tourist destinations in Kedungpari village through culinary tourism festivals. The method used in this study consists of three stages, namely activity preparation, activity implementation, and activity reporting. Research results show that the presence of this culinary tourism festival has a role in optimizing tourist villages